The joint maritime activity between algeria and tunisia in the mediterranean fild during the 17th century AD - boukhalfa, Mohammed chehab Eddine; bin Awmar, hadj moussa (The Algerian Historical Journal, 2026)
This study deals with an aspect of Algerian -Tunisian relations in the Mediterranean during the 17th century, which represented a golden age for the Algerian navy, with the acridness of the development of its activity, front the increase of the acridness of the Islamic and Christian scramble. This situation steered the Algerian and Moroccan sea captains to form a Maghreb fleet for working together from the logic of common motives in cooperation with Tunisian sailors, during to the existence of lot of importance considerations in the development of this partaken activity which appears through joint naval campaigns on the Christian coasts .in addition to the exchange materials support.